Attitudes towards legal and ethical aspects of organ donation among health care workers and general population of Montenegro - Peličić Damir N.; Prelević Vladimir M.; Nejkov Sonja S.; Bogojević Milan D.; Saveljić Mitar M.; Stojanović Vesna D.; Radovanović Snežana M.; Radević Svetlana R. (Srpsko lekarsko drustvo, 2022)
Introduction: Medical and legal problems of organ transplantation are numerous. The donor must be fully and properly informed about all elements regarding the transplantation, and especially about the possible consequences resulting from the removal of tissues and organs, which is an essential ethical problem. Aim: The aim of this research was to determine the attitude of health professionals and the general population in Montenegro towards some of the legal and ethical aspects of organ donation. Material and methods: The research was conducted with the consent of the Ethics Committee of the Clinical Center of Montenegro, in Podgorica number 03 / 01-1504. The sample was formed by random selection and consisted of 400 adult citizens of the city of Podgorica. The research included 200 health workers employed at the Clinical Center of Montenegro in Podgorica and 200 adult citizens of the city of Podgorica. Results: The majority of health workers (84.6%) state that the donor should be the one who gives consent for organ donation for life. Similarly, the vast majority (76%) of the general population believe the same. The largest percentage of participants, more than a third, in both groups, believe that using organs for the wrong purposes is sometimes possible, while almost a quarter of respondents said they did not believe it could happen. The difference in the opinion of health workers and the general population on this issue was not statistically significant (p = 0.522). Conclusion: From our research it can be concluded that both groups of respondents generally believe that the guarantee that organs will be used for the right purposes is the most important factor in organ donation and that the donor is the one who will give consent for living organ donation. The proposed measures need to create a strategy to increase confidence that organ donation will be done only for the right purposes, both in the general population and among health professionals.